Political and Economic Prospects for Mozambique and Angola - Steven Kyle (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2003)
This paper discusses similarities and differences in the political and economic prospects for Angola and Mozambique. Central to the posing of these questions is the meaning and usefulness of putting these two countries in the same category. While both share some elements of a common colonial history, their similarities are in many respects outweighed by their differences. Angola is a country whose economy is dominated by huge oil revenues and whose governing party, the MPLA, recently won a military victory over its long time opposition, UNITA. UNITA, though now much weakened, nevertheless represents the legitimate interests of a large segment of the population, whose home provinces are the most agriculturally favored in the country. Mozambique is a country with many fewer natural resources, but in which the ruling party, FRELIMO, has fully embraced a policy of liberalization and opening of the economy. Its main opposition party, RENAMO, originated as a creature of foreign powers and lost its principal distinguishing feature of anti-Marxism when the governing party itself abandoned Marxism beginning a decade after independence.
Keywords: 330; Politik; Volkswirtschaft; Mosambik; Angola